Alignment of collagen fiber in knitted silk scaffold for functional massive rotator cuff repair. (15th March 2017) - Zheng, Zefeng; Ran, Jisheng; Chen, Weishan; Hu, Yejun; Zhu, Ting; Chen, Xiao; Yin, Zi; Heng, Boon Chin; Feng, Gang; Le, Huihui; Tang, Chenqi; Huang, Jiayun; et al.
Graphical abstract: Abstract: Rotator cuff tear is one of the most common types of shoulder injuries, often resulting in pain and physical debilitation. Allogeneic tendon-derived decellularized matrices do not have appropriate pore size and porosity to facilitate cell infiltration, while commercially-available synthetic scaffolds are often inadequate at inducing tenogenic differentiation. The aim of this study is to develop an advanced 3D aligned collagen/silk scaffold (ACS) and investigate its efficacy in a rabbit massive rotator cuff tear model. ACS has similar 3D alignment of collagen fibers as natural tendon with superior mechanical characteristics. Based on ectopic transplantation studies, the optimal collagen concentration (10 mg/ml), pore diameter (108.43 ± 7.25 μm) and porosity (97.94 ± 0.08%) required for sustaining a stable macro-structure conducive for cellular infiltration was determined. Within in vitro culture, tendon stem/progenitor cells (TSPCs) displayed spindle-shaped morphology, and were well-aligned on ACS as early as 24 h. TSPCs formed intercellular contacts and deposited extracellular matrix after 7 days. With the in vivo rotator cuff repair model, the regenerative tendon of the ACS group displayed more conspicuous native microstructures with larger diameter collagen fibrils (48.72 ± 3.75 vs. 44.26 ± 5.03 nm) that had better alignment and mechanical properties (139.85 ± 49.36 vs. 99.09 ± 33.98 N) at 12 weeks post-implantation. In conclusion, these findings demonstrate the positive efficacy of the macroporous 3D aligned scaffold in facilitating rotator cuff tendon regeneration, and its practical applications for rotator cuff tendon tissue engineering. Statement of Significance: Massive rotator cuff tear is one of the most common shoulder injuries, and poses a formidable clinical challenge to the orthopedic surgeon. Tissue engineering of tendon can potentially overcome the problem. However, more efficacious scaffolds with good biocompatibility, appropriate pore size, favorable inductivity and sufficient mechanical strength for repairing massive rotator cuff tendon injuries need to be developed. In this study, we developed a novel macroporous 3D aligned collagen/silk scaffold, and demonstrated that this novel scaffold enhanced the efficacy of rotator cuff tendon regeneration by inducing aligned supracellular structures similar to natural tendon, which in turn enhanced cellular infiltration and tenogenic differentiation of stem/progenitor cells from both the tendon itself and surrounding tissues. Hence, it can potentially be a clinically useful application for tendon tissue engineering.